2016
DOI: 10.1101/lm.042838.116
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protein synthesis but not β-adrenergic receptors blocks reconsolidation of a cocaine-associated cue memory

Abstract: Previously consolidated memories have the potential to enter a state of lability upon memory recall, during which time the memory can be altered before undergoing an additional consolidation-like process and being stored again as a longterm memory. Blocking reconsolidation of aberrant memories has been proposed as a potential treatment for psychiatric disorders including addiction. Here we investigated of the effect of systemically administering the protein synthesis inhibitor cycloheximide or the b-adrenergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 78 publications
1
26
1
Order By: Relevance
“…Most clinical studies of reconsolidation and substance use in the literature have investigated the β-adrenergic antagonist propranolol with mixed results (Jobes et al, 2015;Lonergan et al, 2016;Pachas et al, 2015;Saladin et al, 2013;Zhao et al, 2011). However, preclinical investigations of garcinol and propranolol in a CS-reactivation paradigm have demonstrated that garcinol may be more effective at reducing reinstatement than propranolol (Dunbar and Taylor, 2016). Similar results were found with propranolol in a USreactivation paradigm in our lab (unpublished preliminary data).…”
Section: Potential Clinical Utility Of Garcinolsupporting
confidence: 73%
“…Most clinical studies of reconsolidation and substance use in the literature have investigated the β-adrenergic antagonist propranolol with mixed results (Jobes et al, 2015;Lonergan et al, 2016;Pachas et al, 2015;Saladin et al, 2013;Zhao et al, 2011). However, preclinical investigations of garcinol and propranolol in a CS-reactivation paradigm have demonstrated that garcinol may be more effective at reducing reinstatement than propranolol (Dunbar and Taylor, 2016). Similar results were found with propranolol in a USreactivation paradigm in our lab (unpublished preliminary data).…”
Section: Potential Clinical Utility Of Garcinolsupporting
confidence: 73%
“…In alcohol‐related studies, it was shown that post‐retrieval injection of propranolol did not affect alcohol‐induced CPP, but did reduce alcohol‐seeking behavior and disrupt the ability of alcohol‐associated cue to act as a conditioned reinforcer, suggesting that the effects of propranolol may be task‐dependent in alcohol dependence (Wouda et al ., ; Font & Cunningham, ; Schramm et al ., ). Interesting, conflicting results from the cocaine SA model were reported such that propranolol either disrupted (Milton et al ., ) or did not affect cocaine reward memory (Dunbar & Taylor, ). A recent study demonstrated that β1‐adrenergic receptor/β‐arrestin 2/ERK‐biased signaling is involved in the reconsolidation of cocaine reward memory (Liu et al ., ).…”
Section: Pharmacological Modulation Of Reconsolidation Of Drug Rewardmentioning
confidence: 99%
“…Specifically, propranolol may be more effective at inhibiting aberrant aversive memories in disorders such as PTSD as opposed to aberrant reward-related memories in disorders such as substance use. This idea is supported by our preclinical findings that systemically administered propranolol does not impair the reconsolidation of cocaine-cue memories in a model of reinstatement (i.e., relapse) to cocaine-seeking behavior in rodents trained to self-administer cocaine (Dunbar and Taylor 2016). …”
Section: Reconsolidation In Healthy Participantsmentioning
confidence: 61%